Celebrating and remembering the festival of September 9: ritual, history, and memory - Ünlü, Ummahan Ceren. (Thesis (M.A.)-Bogazici University. Atatürk Institute for Modern Turkish History, 2007., 2007)
This study scrutinizes the festivals of September 9 for the celebration of Izmir’s Independence Day, both as an official ceremony organized by the nation state and as a commemorative event attended and remembered by the people. A detailed description and analysis of the festival is given with its program, parades, participants, activities, narratives, and symbolic objects. The ritual is analyzed as a totality that has been manipulated by both political elite and ordinary people and that has been affected by the political, historical, local, and festive context. Upon a thorough search of the local newspapers and periodicals of the period, it is argued that September 9 celebrations in the early Republican Turkey were dominated by a national hegemonic narrative which rested on the principles of ethnic homogeneity, national unity and solidarity, monophonic society, and state authority. In this context, the commemoration of September 9 presented the nation state an arena on which the elite had the means of festive symbolism to construct a synchronized collective memory/identity for the citizens. Nevertheless, the analysis of memories of Izmirians through oral history reveals that despite the efforts of the “omnipresent” state, the festival of September 9 has also been an event within which collective and personal memories, different from the hegemonic collective memory, can grow up. The construction of uniform national collective memory could not hinder the obstinate survival of multiple unofficial memories around the commemoration of September 9.